2014
DOI: 10.32738/jeppm.201401.0005
|View full text |Cite
|
Sign up to set email alerts
|

 Management of Interface between Main Contractor and Subcontractors for Successful Project Outcomes

Abstract: There has been increased dependence on subcontracting within the construction industry, the operational relationship between the Main Contractor (MC) and Subcontractor (SC) plays a significant role in successful delivery of projects. Through the literature review this paper argues that despite SCs bring added value to construction projects, the increased reliance on SCs has strained relationships between the MC and SC. Also MCs are more concerned with risk and price reduction which undermine the relationship h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…ABOUT HERE> This study sets out to explore the enablers and barriers to the implementation of SCM at the lower tiers of the construction supply chain, particularly the problematic collaboration between main contractors and subcontractors. Several studies have emphasised the need for collaborative relationships between main contractor-subcontractor organisations (Kale and Arditi, 2001;Cao and Zhang, 2011;White and Marasini, 2014). The aim of this paper is to extend the existing debates on the issue by adopting an alternative approach focusing specifically on the internal SCM organisation of both main contractor and subcontractor organisations, and their direct inter-relationships (Broft, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…ABOUT HERE> This study sets out to explore the enablers and barriers to the implementation of SCM at the lower tiers of the construction supply chain, particularly the problematic collaboration between main contractors and subcontractors. Several studies have emphasised the need for collaborative relationships between main contractor-subcontractor organisations (Kale and Arditi, 2001;Cao and Zhang, 2011;White and Marasini, 2014). The aim of this paper is to extend the existing debates on the issue by adopting an alternative approach focusing specifically on the internal SCM organisation of both main contractor and subcontractor organisations, and their direct inter-relationships (Broft, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It is also suggested that this study is replicated in other countries where collaborative framework agreements display similar characteristics in order for comparative analysis to be undertaken. Lastly, further research should be conducted to examine the performance of supplier chain so that a total performance model can be developed to include the interface between the main contractor and subcontractors, which is considered to be important for successful project outcomes by White and Marasini (2013).…”
Section: Discussionmentioning
confidence: 99%
“…The most successful methods for avoiding contract-related issues were discovered to be well written documents with no ambiguity, right contract procedures, signing after confirming facts, and using sustainable competitive [12]. The main contractor's proactive coordination and good site management is vital for resolving project challenges and completing the project on time [3]. When it comes to getting better know the subcontractors first before subcontract is given, face-to-face communication is viewed as a vital aspect for a good outcome.…”
Section: Problem-solving In the Partnershipmentioning
confidence: 99%
“…Among some of the reasons why the general contractor undertakes the projects with the assistance of third parties are the different specialties, the avoidance of financial strain, and the reduction of dispensable costs [2]. Subcontracting has grown in importance as projects have become more complex as a result of technological improvements and the need for useful resource control to compete successfully [3]. Partnering with subcontractors reduces the contractor's risk exposure [4].…”
Section: Introductionmentioning
confidence: 99%